PENGEMBANGAN AUTHENTIC ASSESSMENT BERBASIS PROYEK PADA MATA KULIAH KEWIRAUSAHAAN - Vahlia, Ira; Sholiha, Sangidatus (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
The entrepreneurship course in economics education already has a module as astudent reference source. The assessment used is through quizzes, UTS and UASwhich contain questions according to achievement indicators in the semesterlearning plan (RPS) where the questions only look at students' cognitive abilitiesbut cannot see affective and psychomotor levels. Lecturers do not yet have authenticassessment tools accompanied by prophetic values with the help of ICT. Thepurpose of this research is to produce authentic assessments in entrepreneurshipcourses that are valid and practical. Sampling by means of purposive sampling. Theinteractive learning video development model uses the 4D development model,namely the stages of defining the problem (define), designing (Design), developing(Develop) and disseminating (disseminate). The data analysis technique used is theanalysis of qualitative data and quantitative data. The results of this study are thatthe product gets a valid and practical category so that it can be used inentrepreneurship learning.Keywords: Authentic Assessment; Enterpreneurship; Project